Challenges and Solutions to Criminal Liability for the Actions of Robots and AI - Vladimír Smejkal; Jindřich Kodl (Advances in Technology Innovation, 2024)
Civil liability legislation is currently being developed, but little attention has been paid to the issue of criminal liability for the actions of robots. The study describes the generations of robots and points out the concerns about robots’ autonomy. The more autonomy robots obtain, the greater capacity they have for self-learning, yet the more difficulty in proving the failure foreseeability when designing and whether culpability or the elements of a specific crime can be considered. In this study, the tort liability depending on the category of robots is described, and the possible solutions are analyzed. It is shown that there is no need to introduce new criminal law constructions, but to focus on the process of proof. Instead of changing the legal system, it is necessary to create the most detailed audit trail telling about the robot’s actions and surroundings or to have a digital twin of the robot.